Bounds on the CP asymmetry in like-sign dileptons from B(0)B*(0) meson decays. - Jaffe, D; Mahapatra, R; Masek, G; Paar, H; Asner, D; Eppich, A; Hill, T; Morrison, R; Briere, R; Chen, G; Ferguson, T; Vogel, H; et al. (2001)
We have measured the charge asymmetry in like-sign dilepton yields from B(0)B*(0) meson decays using the CLEO detector at the Cornell Electron Storage Ring. We find a(0)(ll) identical with[N(l(+)l(+))-N(l(-)l(-))]/[N(l(+)l(+))+N(l(-)l(-))] = +0.013+/-0.050+/-0.005. We combine this result with a previous, independent measurement and obtain Re(epsilon(B))/(1+ the absolute value of epsilon(B)(2)) = +0.0035+/-0.0103+/-0.0015 (uncertainties are statistical and systematic, respectively) for the CP impurity parameter, epsilon(B).